The zoology and The newspaper of the children (Mexico city, 1839-1840) (2013)
In the middle of the 19th century in the city of Mexico developed several projects of scientific magazines addressed to classes in middle and high. One of them was the children´s diary, first Mexican child publishing, which circulated between 1839 and 1840. In this magazine there were several articles of zoology from the instructive, exotic and curious perspectives in order to instruct children in a pleasant way. The objective of the research is to analyze the writings on the wildlife that were aimed at children from a narrative enjoyable and simple language. The study about the zoological spread has a great importance for understanding the ways in which infants of Mexico learnt scientific knowledge outside the classroom in a time when the primary schools had no science subjects. The above mentioned magazine established the bases to extend the capital scientific culture that was developed with strength in the second half of the century in different levels of instruction and in the informal education. It is probable that some of the Mexican scientists were discovering his scientific vocation in the writings of this magazine.